The coping strategies of breast cancer survivors in Iloilo City - Denila, Michelle Pareñas
The study was basically descriptive. It aimed at describing the coping strategies which were preferred and employed by the breast cancer survivors. This also confided some of the experiences that the breast cancer survivors had gone through, and other related aspects like their relationships with people. It made use of case studies, which were helpful in explaining and describing clearly the topic., This study was conducted from November 2005 to January 2006 in Iloilo City. The methods used in gathering the data include questionnaires, in-depth interviews, and participant observation. The respondents were members of Bosom FRIENDS, Inc., and an oncologist. Studies related to the topic were taken mainly from the Internet, and some were from books and journals. It also made used of tape recorder in capturing accurate responses from the respondents. The results primarily considered the subjective responses of the respondents. It also showed that among the varied ways of coping with the illness, the respondents preferred employing religious coping, positive reinterpretation and growth and acceptance, over using unhealthy substances, behavioral disengagement and denial. The respondents also preferred the two major types of copng strategies, the emotion-focused and problem-focused coping, in dealing with breast cancer.